Fandom : identities and communities in a mediated world - Gray, Jonathan (Jonathan Alan), 1975-; Harrington, C. Lee, 1964-; Sandvoss, Cornel (New York, NY : New York University Press, 2017)
A completely updated edition of a seminal work on fans and communities We are all fans. Whether we follow our favorite celebrities on Twitter, attend fan conventions such as Comic Con, or simply wait with bated breath for the next episode of our favorite television drama-each of us is a fan. Recognizing that fandom is not unusual, but rather a universal subculture, the contributions in this book demonstrate that understanding fans--whether of toys, TV shows, celebrities, comics, music, film, or politicians--is vital to an understanding of media audiences, use, engagement, and participatory culture in a digital age. Including eighteen new, original essays covering topics such as activism directed at racism in sports fandom, fan/producer interactions at Comic Con, the impact of new technologies on fandom, and the politics and legality of fanfic, this wide-ranging collection provides diverse approaches to fandom for anyone seeking to understand modern life in our increasingly mediated, globalized and binge-watching world.
Frontmatter -- Contents -- Introduction. Why still study fans? -- 1. The death of the reader?: literary theory and the study of texts in popular culture -- 2. Intimate intertextuality and performative fragments in media fanfiction -- 3. Media academics as media audiences: aesthetic judgments in media and cultural studies -- 4. Copyright law, fan practices, and the rights of the author (2017) -- 5. Toy fandom, adulthood, and the ludic age: creative material culture as play -- 6. Loving music: listeners, entertainments, and the origins of music fandom in nineteenth- century America -- 7. Resisting technology in music fandom: nostalgia, authenticity, and Kate bush's "before the dawn" -- 8. I scream therefore i fan?: music audiences and affective citizenship -- 9. A sort of homecoming: fan viewing and symbolic pilgrimage -- 10. Reimagining the imagined community: online media fandoms in the age of global convergence --- 11. Do all "good things" come to an end?: revisiting Martha Stewart fans after imclone -- 12. The lives of fandoms -- 13. "what are you collecting now?": Seth, comics, and meaning management -- 14. Sex, utopia, and the queer temporalities of fannish love -- 15. the news: you gotta love it -- 16. memory, archive, and history in political fan fiction -- 17. Between rowdies and rasikas: rethinking fan activity in Indian film culture -- 18. Black twitter and the politics of viewing scandal -- 19. Deploying oppositional fandoms: activists' use of sports fandom in the redskins controversy -- 20. Ethics of fansubbing in anime's hybrid public culture -- 21. Live from Hall H: Fan/Producer Symbiosis at San Diego Comic- Con -- 22. Fantagonism: Factions, Institutions, and Constitutive Hegemonies of Fandom -- 23. The Powers That Squee: Orlando Jones and Intersectional Fan Studies --- 24. Measuring Fandom: Social TV Analytics and the Integration of Fandom into Television Audience Measurement -- About the Contributors -- Index
Elektronická reprodukce.
Keywords: fanouškovství; fanoušci; masová kultura; subkultura; fandom; fans (persons); popular culture; subculture; e-knihy online; e-books online